Indoor thermal performance of an office building using Conventional Brick Versus Interlocking Compressed Earth Brick (ICEB) wall - Abdullah, Abd Halid; Abu Bakar, Siti Khatijah; Abdul Rahman*, Ismail (ZW Publisher, 2013)
In recent years, the growing interest in using earth as modern wall material has mushroomed. However, the study on its indoor thermal environmental impact is still lacking Thus, this study was meant to investigate and compare the resulting indoor thermal performance of an office building due to common brick (CB) and interlocking compressed earth brick (ICEB) as wall materials. The comparison was based on the results of thermal simulation using ECOTECT program. It was found that by using ICEB for wall construction could possibly reduce the indoor operative temperature of office building by 1°C during the day. Moreover, the temperature distribution indicates that the percentage of indoor operative temperature remains in comfort condition during the working hours increase at about 22% on the ground floor and 30% on the first floor respectively, throughout the year. It is evident that ICEB provides a better indoor thermal performance than that of CB, and thus it has greater potential as alternative wall material in improving the indoor environmental condition during the day particularly in office building.